A DECADE OF PROGRESS: A BIBLIOMETRIC ANALYSIS OF RESEARCH TRENDS IN PROFESSIONAL DEVELOPMENT FOR MIDDLE LEADERS IN EDUCATION (2014-2023) - Nur Suhaila Ahmad; Aziah Ismail; Muhammad Nidzam Yaakob, (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2024)
During an era of rapid change and progress in education, the professional growth of middle leaders has become crucial for successful school administration and student achievement. Nevertheless, there needs to be a more thorough comprehension of worldwide research patterns in this particular area. This study aims to fill this void by examining the patterns of professional growth for middle leaders in the field of education between the years 2014 and 2023. The research conducted an in-depth examination of 287 papers indexed in Scopus. Innovative approaches such as co-citation analysis and keyword co-occurrence mapping utilizing VOSviewer software were employed. The study identified important themes, regional contributions, and emerging areas of interest. The findings reveal a significant increase in publications, primarily from the United States, United Kingdom, and Australia. There is also a noticeable trend towards comprehensive development strategies, including leadership abilities, psychological well-being, and data-driven decision-making. The study identifies deficiencies in research conducted in non-Western settings and emphasizes the necessity for additional investigation on digital leadership skills. These insights provide useful assistance for policymakers and educational leaders in designing customized professional development programs. They highlight the significance of adaptable, culturally sensitive leadership development strategies in effectively navigating the intricacies of contemporary educational settings.